Modeling a complete Stirling engine. (1st February 2015) - Paul, Christopher J.; Engeda, Abraham
Abstract: The assumptions of second order Stirling engine models were reviewed. An ideal adiabatic plus simple heat exchanger model was developed. The model included the external components such as the fan, combustor, and preheater. The external heat transfer to the engine heater was modeled using a log-mean-temperature difference for a constant tube surface temperature. The performance of the model of the external components compared reasonably well to experimental data. The performance of the complete engine model was also compared to experimental data of the GPU-3. By adjusting the flow dissipation to better account for unsteady flow conditions and compressibility effects, the complete engine model was able to predict engine power and brake specific fuel consumption to within ±14% over a wide range of engine speeds and mean pressures. This analysis and others suggest that second order models of Stirling engines need to account for the gradient of the divergence of velocity term in the compressible momentum equation if the mean engine pressure is low enough (less than 3.0 MPa) and the engine speed is high enough (above 30 Hz). Highlights: Ideal adiabatic plus simple heat exchanger model developed. External heat transfer modeled using log-mean-temperature-difference. Model performance validated by using data for GPU-3 over range of speeds and pressures. Flow dissipation is amplified at engine pressures less than 3.0 MPa and speeds greater than 1500 rpm. Flow dissipation adjusted to better account for these extra losses at low pressures and high speeds.